Diabetic Complications among Adult Diabetic Patients of a Tertiary Hospital in Northeast Ethiopia - Asrat Agalu Abejew; Abebe Zeleke Belay; Mirkuzie Woldie Kerie (Hindawi Limited, 2015)
Background. The diabetic complications are becoming common community problems. The outcomes of diabetic complications are increased hospitalization, increased direct patient costs, and mortality. In Dessie, the prevalence of the diabetic complications is not well studied so far. Thus, the aim of this study is to assess prevalence of diabetic complications and associated factors among adult diabetic patients of Dessie Referral Hospital, Northeast Ethiopia. Methods. Cross-sectional study was conducted in the diabetic clinic of Dessie Referral Hospital from April to May 31, 2013. All diabetic patients who visited the clinic during the study period were included. Data was collected using interview guided self-administered questionnaire. Presence of complications and the type of medications the patient was on were identified through review of patient records. Data were cleaned, coded, and entered into SPSS for Windows version 17.0. Descriptive statistics and chi-square tests were carried out to meet the stated objective. The Results. Overall 129 (59.7%) of the patients were found to have been affected by one or more of the diabetic complications. Complications were identified mainly among type II diabetic patients. The age of patients (P value-0.048), type of diabetes (P value-0.00), and medication (P value-0.00) were strongly associated with the occurrence of diabetic complication but self-reported adherence, attitude, and knowledge level of patients and the family history were not associated with the presence of complication. Conclusion. The prevalence of complications among diabetic patients in Dessie Referral Hospital was high. Targeted counseling and health information provision to the patients by the clinical staff will be helpful in reducing avoidable morbidity and mortality in the patients.